Visual palatability of food dishes in color appearance, glossiness and convexo-concave perception depending on light source (2015)
This study aims to reveal visual factors which determine the visual palatability of food dishes. We conducted subjective experiments under different light sources, and examined the correlation between the visual palatability and the visual factors, color appearance, glossiness, and convexo-concave perception. We prepared twelve kinds of food dishes, and measured the chromaticity values of all dishes under six kinds of light sources. Next, we transformed the measured data into their respective RGB values. This color management process ensures that the digital images can be displayed with the same chromaticity values as the real objects so that participants can observe the same visual stimuli with no olfactory cues. Twenty participants observed one of the images for one minute, and evaluated the "visual palatability", and answered subjectively three factors, "color appearance", "glossiness" and "convexo-concave perception". As a result, it was revealed that higher correlated color temperature light makes the dishes more palatable, suggesting that the color appearance is an important visual factor for the visual palatability of food dishes. In addition, it was shown that the visual palatability of the raw food dishes and the dishes with sauce can be affected by both color appearance and glossiness depending on the light source.